Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fmicb.2021.720437
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Inactivated QazCovid-in Vaccine: Protective Efficacy of the Vaccine in Syrian Hamsters

Abstract: In March 2020, the first cases of the human coronavirus disease COVID-19 were registered in Kazakhstan. We isolated the SARS-CoV-2 virus from clinical materials from some of these patients. Subsequently, a whole virion inactivated candidate vaccine, QazCovid-in, was developed based on this virus. To develop the vaccine, a virus grown in Vero cell culture was used, which was inactivated with formaldehyde, purified, concentrated, sterilized by filtration, and then adsorbed on aluminum hydroxide gel particles. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…In Kazakhstan, the technology for production of formaldehyde-inactivated, adjuvanted with aluminium hydroxide, whole-virion vaccine QazCovid-in® against COVID-19 has been developed, and preclinical studies 27 as well as phases 1/2 clinical trials of the vaccine are now completed. 28 The QazCovid-in® vaccine is proven to be safe, well-tolerated, and immunogenic in two age groups, 18–49 and ≥50 years.…”
Section: Introductionmentioning
confidence: 99%
“…In Kazakhstan, the technology for production of formaldehyde-inactivated, adjuvanted with aluminium hydroxide, whole-virion vaccine QazCovid-in® against COVID-19 has been developed, and preclinical studies 27 as well as phases 1/2 clinical trials of the vaccine are now completed. 28 The QazCovid-in® vaccine is proven to be safe, well-tolerated, and immunogenic in two age groups, 18–49 and ≥50 years.…”
Section: Introductionmentioning
confidence: 99%
“…It is a two‐dose, intramuscular, and formalin‐inactivated vaccine adjuvanted with aluminum hydroxide. 56 Phase 1/2 clinical trial (NCT04530357) was conducted in two parts to evaluate the safety, tolerability, and immunogenicity of vaccine based on the comparison of antibody titers in serum samples before and after vaccination, which was measured by microneutralization test (MNA) and enzyme linked immunosorbent assay (ELISA) tests. QazVac vaccine testing on 44 subjects aged 18–50 years demonstrated its favorable tolerability in phase 1 part of phase 1/2 clinical trial, and MNA showed seroconversion in 100% of subjects after two doses of the vaccine.…”
Section: Qazcovid‐in Vaccinementioning
confidence: 99%
“…QazCovid‐in, commercially known as QazVac vaccine, was developed by the Research Institute for Biological Safety Problems in Kazakhstan. It is a two‐dose, intramuscular, and formalin‐inactivated vaccine adjuvanted with aluminum hydroxide 56 . Phase 1/2 clinical trial (NCT04530357) was conducted in two parts to evaluate the safety, tolerability, and immunogenicity of vaccine based on the comparison of antibody titers in serum samples before and after vaccination, which was measured by microneutralization test (MNA) and enzyme linked immunosorbent assay (ELISA) tests.…”
Section: Qazcovid‐in Vaccinementioning
confidence: 99%
“…The first human cases of coronavirus infection COVID-19 (coronavirus disease 2019) were recorded in the Republic of Kazakhstan (RK) in mid-March 2020 ( 6 ). According to World Health Organization data, on 14 June 2022, a total of 1,395,068 confirmed cases were registered in the Republic of Kazakhstan, resulting in 19,017 deaths ( 7 ).…”
Section: Announcementmentioning
confidence: 99%